(untitled) (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To analyze the components that mediate the employability of people with visual disabilities who graduated from university degrees in Administration and Management in Human Resources, Sociology, Psychology, and Career Guidance in Costa Rica in the period 2021-2024. Methodology: It is carried out from a naturalistic paradigm with a phenomenological approach, based on a qualitative research method, in which five participants were selected through convenience sampling, considering three inclusion criteria: that they have a situation of visual disability, that they are graduates of a university in Costa Rica, and that they are currently working. Results: Employability has a transversal character that encompasses three components: university education, insertion, and job permanence. Since the basic functions of universities foster the development of skills that have a relationship and a contribution to the personal and working conditions of the people under study at the time of entering the labor market, this influences the commitment and job satisfaction they have in their jobs. Conclusions: University education significantly contributes to developing soft skills for people with visual impairments. Both personal and work conditions foster a transition of personal and professional development in the population. Some elements affect the employment permanence of the population, such as job satisfaction and commitment.